2019
DOI: 10.1021/acsnano.8b07231
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Functionization Elevates Transcytosis of Nanogranules across Epithelium by Triggering Polarity-Associated Transport Flow and Positive Cellular Feedback Loop

Abstract: Overcoming the epithelial barriers to enhance drug transport is a focused topic for gastrointestinal, intratracheal, intranasal, vaginal, and intrauterine delivery. Nanomedicines with targeting functionization promote such a process owing to specific ligand–receptor interaction. However, compared to the cell uptake of targeting nanotherapies, currently few studies concentrate on their transcytosis including endocytosis for “in” and exocytosis for “out”. In fact, the cellular regulatory mechanism for these path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…Early endosomes act as a sorting machine and can carry the cargos to specific subcellular organelles, to recycling endosomes for apical recycle recycled, to basolateral compartment for releasing. [16][17][18] Besides, early endosomes can mature to late endosomes (also called multivesicular body). NMs that failed to escape from the endosomes face degradation in the lysosome.…”
Section: Endocytosis Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Early endosomes act as a sorting machine and can carry the cargos to specific subcellular organelles, to recycling endosomes for apical recycle recycled, to basolateral compartment for releasing. [16][17][18] Besides, early endosomes can mature to late endosomes (also called multivesicular body). NMs that failed to escape from the endosomes face degradation in the lysosome.…”
Section: Endocytosis Pathwaysmentioning
confidence: 99%
“…NMs that failed to escape from the endosomes face degradation in the lysosome. [16][17][18] According to the proteins involved, endocytosis pathways are generally classified into phagocytosis and pinocytosis. 19 Pinocytosis is ubiquitous in almost any eukaryotic cell and is employed by NMs when entering into the tumor cell.…”
Section: Endocytosis Pathwaysmentioning
confidence: 99%
“…There are however reports of TfR-mediated transcytosis being explored for oral delivery of biologics via a Tf recombinant fusion protein approach [15] or Tf conjugation to therapeutic macromolecule [16]—both these approaches have shown evidence and potential for the use of TfR-mediated transport as a strategy to enhance the intestinal absorption (i.e., in the apical-to-basolateral direction) of biologics. Importantly, a recent landmark study clearly showed a complete and enhanced apical-to-basolateral transcytosis of Tf-functionalised nanogranules in Caco-2 cells, with Tf modification upregulating the expression of trafficking-related (endocytosis and transcytosis) proteins [17].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental study of this nature is imperative to assess the possibility that TfR-mediated transcytosis may be utilised to facilitate intestinal translocation of nanomedicines. This is important as, with the exception of two studies [17,18], TfR-mediated transcytosis has not been investigated for intestinal delivery of nanosystems. We show here that TfR targeting of NP significantly improves their uptake into intestinal epithelial cells (Caco-2), as well as translocation across cell monolayers serving as an in vitro intestinal model.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, we explored the endocytic mechanisms of NPs in Madin-Darby canine kidney (MDCK) cells, as these cells represent an ideal in vitro epithelial model owing to their polarity, tight junction formation, and relatively thin mucus layer. 17 Moreover, the neuroprotective effects of NPs were evaluated using human neuroblastoma SH-SY5Y cells, a neuron-like cell model that has been widely used to evaluate intracellular events linked to neurotoxic insults. To extend this work, we then employed a zebrafish model system in order to explore the ability of coumarin 6 (C6)-labeled NPs (C6-NPs) to cross specific biological barriers in vivo.…”
Section: Introductionmentioning
confidence: 99%